Correlation and path analysis of assessment methodologies of bone quality from brown egg layers at final of the production cycle - Túlio Leite Reis; Felipe Dilelis; Letícia dos Santos Lima; Pedro Henrique Ferreira da Silva; Pollianna Luciene da Silva Soares; Ligia Fatima Lima Calixto (Acta Scientiarum. Animal Sciences, 2022)
This study aimed to investigate direct and indirect correlations of methodologies of bone quality analysis from brown egg layers, at final of the production cycle. Twelve femurs of Dekalb Brown laying hens, euthanized at 85-week-old, were assessed to evaluate breaking strength (BS), Seedor index (SI), mineral matter (MM), calcium (Ca) and phosphorus (P) contents, besides cortical (CorD), medullar (MedD) and epiphysis (EpiD) diameters. Correlations and path analysis were obtained with the aid of SAS® University (p ≤ 0.05). The BS directly represented the bone quality and was compared to other methodologies. Greater linear correlations occurred between BS and MM (r = 0.82), MM and Ca (r = 0.72), and BS and Ca (r = 0.70). The MM content displayed the greatest direct effect on the BS (r = 0.53). The Ca content showed a reduced direct effect on the BS (r = 0.18), with indirect effects through MM content (r = 0.44) and EpiD (r = 0.15), however, presented a great total correlation (r = 0.78). Determination of mineral matter content is the main methodology associated with femur breaking strength from brown egg layers at final of the productive cycle. Because of that, this methodology is more reliable to determine bone quality.